"It was a good… good, bad situation.": Cameroonian fathers' experiences of childbirth in Sweden. (October 2022) - Nges, Benedicta; Jonsson, Ulrika; Crang-Svalenius, Elizabeth; Thies-Lagergren, Li
Abstract: Introduction: In Sweden, partner's presence during childbirth is generally recommended. However, cultural values and norms in some immigrant societies can be an obstacle to this. Objective: To examine the experiences of Cameroonian fathers during their women's labour and childbirth in Sweden. Design: An exploratory qualitative study with semi-structured interviews were used for data collection and analysed with thematic content analysis. Setting: Scania County, South of Sweden. Participants: Twelve fathers accessed through sociocultural associations. Findings: Conflicting feelings was identified as the main category, which was further divided into three subcategories; (a) Ambivalent feelings, (b) Cooperation and finding one's place in a foreign area and (c) Knowledge, insight and transition . Key conclusion: Pre-knowledge about childbirth, cooperation between fathers and medical staff are key factors which impacted the labour/childbirth experiences of Cameroonian fathers living in Southern Sweden. Clinical implications: This study emphasises the importance to individualise information and support given to fathers during labour and childbirth.